Utilizing Instagram Social Media Content as a Correct Hamster Care Educational Media - Suhartono, Natasya Priscilla; Tjandrawibawa, Paulina (Jurnal VICIDI, 2022)
Little Milku is an educational media that discusses about proper hamster care because there’s still a lot of misconception about hamster care in Indonesia. Little Milku was just formed in early 2022 so awareness of the brand is still low because there is still no content uploaded to attract the audience. This study aims to find out how to design content that is effectively used as an educational medium for hamster care. Instagram was chosen as the main media to reach Little Milku's target audience, which is Gen Z teenage girls aged 18-24 years because of its main feature that utilizes content in the form of photos and videos. This study uses secondary data collection methods through literature studies from books and journals that discuss promotional media, social media marketing, cartoons and comics. Data was also obtained from qualitative primary collection methods through interviews with expert users in the field of illustration and extreme users who are Little Milku followers. In addition, data was also obtained quantitatively through a survey of 155 Little Milku Instagram followers. From this research, it was found that in order to create content that can be optimally used as an educational medium, it is necessary to provide illustrations in a cartoon visual style with colors that match the tastes of the target audience to focus the attention of the target audience. The content created must also have values that are in line with Little Milku's main goal, which is to become a fun hamster care educational platform. Keywords: Content, Instagram, Education, Hamster Care